Credit conditions and consumption, house prices and debt: What makes Canada different? - John Muellbauer; Pierre St-Amant; David Williams (Bank of Canada, 2015)
There is widespread agreement that, in the United States, higher house prices raise consumption via collateral or possibly wealth effects. The presence of similar channels in Canada would have important implications for monetary policy transmission. We trace the impact of shifts in non-price household credit conditions through joint estimation of a system of error-correction equations for Canadian aggregate consumption, house prices and mortgage debt. We find strong evidence that, after controlling for income and household portfolios, easier credit conditions raise house prices, debt and consumption. However, unlike in the United States, housing collateral effects on consumption are absent. Given credit conditions, rising house prices increase the mortgage down-payment requirement and reduce consumption, although there is evidence for some attenuation of this effect over the 2000s. We also find that high and rising levels of both house prices and debt since the late-1990s can be mostly explained by movements in incomes, housing supply, mortgage interest rates and credit conditions, suggesting that the outlook for house prices and debt could depend mainly on the future paths of these variables.
Keywords: E02; E21; E44; G21; R21; R31; 330; Credit and credit aggregates; Domestic demand and components; Economic models; Financial institutions; Financial stability; Financial system regulation and policies; Housing; Transmission of monetary policy